Hungry for Hungary: examples of tobacco industry's expansionism - Szilágyi, T; Chapman, S (Central European journal of public health, 2003)
OBJECTIVE: To give an overview of available internal tobacco industry documents on the transnational tobacco companies' (TTCs) efforts to enter the new market of the emerging democracy of Hungary and how it developed allies in its efforts at resisting tobacco control regulations. METHOD: Internal tobacco industry documents relevant to Hungary, available on the World Wide Web, were searched between 26 July and 30 November 2001. Documents on the identification of Central and Eastern Europe (CEE) as a great market potential have been reviewed; another set of reviewed documents are of particular relevance to Hungary, as they indicate who the main partners of the industry are. CONCLUSIONS: TTCs not only invaded the markets of the fragile new CEE democracies by making their product widely available, but also introduced sophisticated lobbying and marketing tactics. TTCs will try to shape the country's regulatory framework in a manner to help increase their profits. The fiercer the reaction of TTCs against a planned regulatory measure is, the more impact on the health of the population could be expected from the introduction and enforcement of that measure.
Keywords: řízení společenských procesů; dokumentace; Democracy; Internationality; lidé; politika; internacionalita; marketing; tabákový průmysl; Internet; Marketing; demokracie; Politics; Hungary; Maďarsko; internet; Social Control Policies; Documentation; Tobacco Industry; Humans